Perceptions of English foreign language university students towards the online freshman composition course - Alrishan , Amal Mohammad Husein (Journal of Education and e-Learning Research, 2024)
The purpose of this research is to explore the perceptions of English Foreign Language University students towards online freshman composition courses at the university. The study aims to explore students’ perspectives on the course and evaluate the reliability, convergent validity and discriminant validity of the construct among Omani EFL university students. Data were collected from 276 Omani EFL university students who were enrolled in freshman composition courses using a quantitative survey methodology. Participants rated their experiences using a five-point scale. The study used both exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) conducted with Analysis of Moment Structures (AMOS) 26 to achieve its research objectives. The results of this research provide substantial support for the validity and reliability of the multidimensional construct representing students’ perceptions. Additionally, the results of the study demonstrate that the measurement is consistent across various academic levels indicating programme invariance. A five-factor model that accurately represents students’ opinions on online freshman composition courses has been developed in this study. The outcomes contribute to the theoretical understanding of evaluating students’ perceptions of the course and hold practical implications for enhancing the teaching and design of similar courses.